2014
DOI: 10.1177/1071100714563536
|View full text |Cite
|
Sign up to set email alerts
|

Interposition Bone Block Arthrodesis for Revision Hallux Metatarsophalangeal Joint Surgery

Abstract: Level IV, retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Successful use of allograft has been described for managing high-risk patient populations previously in multiple joints in the foot, and even in the setting of revision first metatarsophalangeal joint arthrodesis. 17,19 Our findings are consistent with reports that the use of structural allograft does not increase the risk of nonunion in arthrodesis procedures.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Successful use of allograft has been described for managing high-risk patient populations previously in multiple joints in the foot, and even in the setting of revision first metatarsophalangeal joint arthrodesis. 17,19 Our findings are consistent with reports that the use of structural allograft does not increase the risk of nonunion in arthrodesis procedures.…”
Section: Discussionsupporting
confidence: 90%
“…12,21 Various techniques for augmentation with bone grafting have been discussed in both primary and revision arthrodesis. 3,17,19 In addition, over the past several years there have been additional studies looking at the use of orthobiologics in both primary arthrodesis procedures and treatment of fracture nonunion. 4,24…”
Section: Introductionmentioning
confidence: 99%
“…A total of ten articles met the eligibility criteria from the 180 articles initially retrieved from the five databases [3,[21][22][23][24][25][26][27][28][29]. This systematic review utilized a PRISMA diagram to visually depict the search process from initial search to final article inclusion (Figure 1).…”
Section: Search Resultsmentioning
confidence: 99%
“…Hamilton et al found 18% of non-union in Lapidus arthrodesis using a autogenous bone block (38) . When using cadaveric donor bone to fill defects in metatarsophalangeals fusions, Luke et al observed pseudoarthrosis in 13% of the sample and Malhotra et al observed it in 12% (39,40) . Clinical and radiographical fusion was noted in this study's patient at three months, with at least 80% of trabecular formation through each surface noted.…”
Section: Discussionmentioning
confidence: 99%